231k views
6 votes
Elimination Problem Please I Need HELP this makes me want to die lol

3y= -5x-3
y= -x+1

HELP ME PLEASE I BEGGGG

User Goul
by
5.8k points

1 Answer

8 votes

Answer:

(-3, 4)

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

  • Multiplication Property of Equality
  • Division Property of Equality
  • Addition Property of Equality
  • Subtraction Property of Equality

Algebra I

  • Terms/Coefficients
  • Coordinates (x, y)
  • Solving systems of equation using substitution/elimination

Explanation:

Step 1: Define Systems

3y = -5x - 3

y = -x + 1

Step 2: Rewrite Systems

Equation y = -x + 1

  1. [Multiplication Property of Equality] Multiply everything by -3: -3y = 3x - 3

Step 3: Redefine Systems

3y = -5x - 3

-3y = 3x - 3

Step 4: Solve for x

Elimination

  1. Combine 2 equations: 0 = -2x - 6
  2. [Addition Property of Equality] Add 6 on both sides: 6 = -2x
  3. [Division Property of Equality] Divide -2 on both sides: -3 = x

Step 5: Solve for y

  1. Define original equation: y = -x + 1
  2. Substitute in x: y = -(-3) + 1
  3. Simplify: y = 3 + 1
  4. Add: y = 4
User BakriOnFire
by
5.2k points